Analisis Laporan Keuangan PT Unilever Tbk - Ilma Amelia; Syaharani Mutia Sinulingga; Olipian Resky Pernando; Naiya Aulia Putri; R. Septian Armel; Billy Nurmanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Financial report analysis is an analysis between numbers in financial reports and other numbers that have meaning or can explain a trend or event. So in this research we aim to describe and evaluate the financial performance of PT. Unilever Indonesia Tbk. The focus of the problem discussed in this research is the condition of PT's financial performance. Unilever Indonesia Tbk. from 2020 to 2023. The analysis was carried out using index number trend series analysis for the company. The method used in this research is quantitative and qualitative research with a descriptive approach, through calculations of quantitative data in the form of annual financial reports (secondary data) from 2020-2023. The result of this analysis is The analysis shows that the company's sales and revenue have increased from year to year, indicating success in its business. This increase is due to an increase in consumer spending and cash transactions. However, the company faces challenges such as time-related depression, financial losses, technological issues, and changing market conditions.